Thou Shalt Not Consume the Rivals: Rivalry Effects on Behavioural Intentions of Sports Celebrity Brand Offerings - Zarkada, Anna K.; Tzoumaka, Eugenia (My University, 2017)
Since, humans’ inclusion in the list of consumption items (Solomon, 2006) the celebrity brand notion has been gaining academic ground. Celebrity brands, “the subject[s] of marketing communications efforts” (Carlson & Donavan, 2013, p. 193) and media objects, are also viewed as “cultural intermediaries” (Brownlie, Hewer, & Kerrigan, 2015, p. 454). Thanks to their appeal, celebrities not only do sell themselves as objects but also as instruments (Zarkada, Tzoumaka, Siomkos, & Panigyrakis, 2014) and most importantly the lifestyle they follow thus transforming culture into an economic sphere of its own(Moeran, 2003). On the basis of McCracken’s meaning transfer theory (1989) celebrities carry a multitude of meanings. For sports celebrities such meaning stems from the team a player currently competes for, has competed in the past or has linked his career with. Teams are a source of power to their athletes (Carlson & Donavan, 2008) and fan identification with them is associated with positive sports celebrity brand outcomes (Carlson & Donavan, 2013; Tzoumaka, Tsiotsou, & Siomkos, 2014). Accordingly, but viewing the team effect oppositelyas in the out-group favouritism (Tajfel & Turner, 1986), rivalry, has been identified as a meaning that may be transferable to both sponsors (Bee & Dalakas, 2015) and athletes(Chien, Kelly, & Weeks, 2016). The present study investigated whether consumer response to numerous and distinct sports celebrity related offerings would vary in the presence of rivalry. The European football, which is considered to be the King of sports accounting for 27.1% of the accumulative sports business revenues globally (Collignon & Sultan, 2014) and in which severe rivalries between teams are evident (Bergkvist, 2012) was selectedas the context of the study.
Keywords: rivalry; team identification; sports celebrity brands; football; sports marketing